VISUALISASI PESAN GIZI SEIMBANG MENGGUNAKAN ASPEK SPATIAL, TEMPORAL, LIVE ACTION, DAN TYPOGRAPHY - Qudratina, Qudratina; Antoni, Condra (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2018)
Public Service Advertisement have an important role in disseminating information to public. Along with the development of information and communication technology, the delivery of information such as Public Service Advertisement is also more interactive and modern. This is seen by the number of Public Service Advertisement using motion graphic techniques. Motion graphics are graphics that use video or animation to create the illusion of motion or transformation. Motion graphic based of Public Service Advertisement is simple in messaging, easy to absorb information and more appealing to the public. One of the information presented using motion graphic of Public Service Advertisement is about â€œPedoman Gizi Seimbangâ€. Motion graphics of Public Service Advertisement raises the topic of â€œPedoman Gizi Seimbangâ€ which is aimed at the community, especially housewife who acts as the observer of foof consumed by all family. Desaigned of â€œPedoman Gizi Seimbangâ€ applied some aspects in motion graphics. These aspects are spatial, temporal, live action, and typography. The research will use Villamil-Molina (1997) development method which each stage is interconnected and has an important role. Stages of the method are development, pre-preduction, production, post-production, and delivery. The software used in this research is Adobe Illustrator CS6, Adobe After Effects CC 2018, and Adobe Premiere CS6. The results of this research indicate that motion graphic Pedoman Gizi Seimbang that apply spatial, temporal, live action, and typography aspects get response â€œSangat Setujuâ€ from respondents which is proved by the final value of interpretation of 83.62%.